Preparation of starch-based full-biomass green adhesive with strong adhesive strength and hot water soaking resistance and application of starch-based full-biomass green adhesive in wood processing

By combining high-amylose starch and tannic acid and treating with KH560, a starch-based adhesive resistant to hot water immersion was prepared, which solved the problem of insufficient adhesion of starch-based adhesives in humid environments. This resulted in plywood with improved hot water immersion resistance and environmentally friendly production, making it suitable for various wood processing applications.

CN121006170APending Publication Date: 2025-11-25GUANGZHOU UNIVERSITY

Patent Information

Application Number
CN202511158988.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing starch-based adhesives have insufficient adhesion in humid or hot water environments, making it difficult to meet the hot water immersion resistance requirements of the national standard GB/T 9846-2015 for Class II plywood. Furthermore, the modification process is complex and costly, making it difficult to promote and apply them.

Method used

Starch-based adhesives were prepared by using high-amylose starch and tannic acid as raw materials, adjusting the pH value and heat treatment. γ-glycidoxypropyltrimethoxysilane KH560 was then applied to the wood surface to form a dense network structure, improving adhesion and hot water resistance.

Benefits of technology

The prepared plywood can maintain good adhesion after being soaked in room temperature water or 60°C hot water for a long time, meeting national standards. The process is simple, environmentally friendly and non-toxic, and suitable for processing a variety of wood products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121006170A_ABST
    Figure CN121006170A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wood adhesives, and particularly relates to preparation of a starch-based full-biomass green adhesive with high adhesive strength and hot water soaking resistance and application of the starch-based full-biomass green adhesive in wood processing. The method comprises the following steps: preparing a starch-based adhesive from high amylose and tannic acid, treating the surface of wood by using KH560, coating a wood board with the starch-based adhesive, pressing and drying to obtain the plywood. Even if the plywood is soaked in water of 30 DEG C or hot water of 60 DEG C for 3 hours, the plywood does not have glue failure, the shearing strength is higher than 1.0 MPa when the plywood is torn, and the use requirements of national standard II-type plywood are met.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of wood adhesives, and particularly relates to preparation of a starch-based full-biomass green adhesive with strong adhesive force and water immersion resistance and application thereof in wood processing. BACKGROUND

[0002] In the wood processing industry, traditional adhesives such as urea-formaldehyde resin, phenol-formaldehyde resin and polyurethane are mainly derived from fossil fuels. These adhesives have excellent performance, and can maintain excellent adhesive force even in a humid or water immersion environment, and thus are widely used in the production of plywood, particle board and medium-density fiberboard. However, these adhesives will inevitably release harmful gases such as formaldehyde during synthesis and use, which poses a potential threat to human health. In view of this, the development of green and environmentally friendly bio-based (such as protein, tannin, lignin, chitosan and starch) adhesives has attracted increasing attention.

[0003] Among the numerous bio-based adhesives, starch stands out due to its low price. Starch is rich in hydroxyl groups, which can form hydrogen bonds with cellulose on the surface of wood, thereby achieving the bonding of wood boards. However, the multi-hydroxyl structure of starch also makes it have strong hydrophilicity, which leads to a sharp weakening of the adhesive ability of starch-based adhesives whether they are immersed in water or are in a humid environment for a long time, thereby greatly restricting their application range.

[0004] In order to improve the water resistance of starch, at present, it is mainly realized by modifying starch. On the one hand, by introducing hydrophobic groups (such as oxidation, esterification, etc.) to the starch chain to shield the hydroxyl group, thereby reducing its hydrophilicity; on the other hand, by using covalent bond or non-covalent interaction (such as grafting, crosslinking, etc.), the starch chain forms a dense three-dimensional network, thereby reducing the penetration speed of water into the colloidal network. Through the above methods, starch-based wood adhesives that can withstand room temperature water soaking have been successfully developed. However, the national standard GB / T 9846-2015 requires that type II plywood can withstand 60℃ hot water soaking. However, due to the significant increase in kinetic energy of starch chains in 60℃ hot water, it is difficult to maintain the original dense three-dimensional network structure, so most starch-based adhesives cannot meet this requirement. For example, the applicant's previous invention patent application CN115340832A uses high amylose starch and urea-formaldehyde resin as raw materials to prepare a starch-based water-resistant flame-retardant adhesive, which improves the water resistance of the starch-based adhesive to some extent, but the plywood will delaminate when soaked in 60℃ hot water. In addition, although some researchers have developed starch-based adhesives that can withstand hot water soaking, the modification reaction is complex, the synthesis is difficult, and the actual application effect is not ideal. For example, Hou et al. used sodium periodate to oxidize starch, and then reacted with polyurea compound to obtain crosslinked oxidized starch-hexanediamine urea adhesive, which can be used for plywood and can withstand hot water soaking (Hou MH, Lei H, Zhou XJ, et al. Preparation and characterization on the eco-friendly corn starch based adhesive of with salient water resistance, mildew resistance [J]. International Journal of Biological Macromolecules, 2024, 269.). This method is complex, the cost of raw materials is high, and the synthesis is difficult, which is not conducive to popularization and application.

[0005] In view of the above, it is necessary to develop a starch-based adhesive with strong adhesion and capable of resisting 60℃ hot water soaking for wood processing. SUMMARY

[0006] In order to overcome the shortcomings of the prior art, the present application provides a preparation of a starch-based full-biomass green adhesive with strong adhesion and hot water resistance and its application in wood processing. The plywood prepared by the present application can still maintain good adhesion after long-term soaking in room temperature water or 60℃ hot water, meeting the use requirements of national standards for type II plywood.

[0007] In order to achieve the above purpose, the technical scheme adopted by the present application is:

[0008] The first aspect of this invention provides a method for preparing a starch-based, all-biomass green adhesive with strong adhesion and resistance to hot water immersion, the preparation method comprising the following steps:

[0009] (1) Add high amylose to NaOH solution to obtain starch emulsion;

[0010] (2) Add CaCl2 solution to starch emulsion;

[0011] (3) Add tannic acid solution to starch emulsion in step (2), adjust pH value, heat and keep warm to make hot starch paste;

[0012] (4) Add NaOH solution to hot starch paste, adjust pH to 9-10, keep warm and stir for a certain time to obtain starch-based whole biomass green adhesive with strong adhesion and resistance to hot water soaking.

[0013] Furthermore, in step (1), the high amylose refers to natural starch with an amylose content of more than 50% in the starch granules.

[0014] Further, in step (1), the mass concentration of the NaOH solution is ≥1%, and the mass ratio of the high amylose to the NaOH solution is ≤3:5.

[0015] Further, in step (2), the mass concentration of the CaCl2 solution is ≥5%, and the mass ratio of CaCl2 to high amylose is ≥5%.

[0016] Furthermore, in step (3), the mass ratio of tannic acid to high amylose is ≥1:5, and the pH value is 6.5-7.

[0017] Furthermore, in step (3), the heating temperature is 98°C and the heat preservation time is 30 min.

[0018] Furthermore, in step (4), the temperature of the heat preservation is ≥75℃ and the heat preservation time is ≥30min.

[0019] A second aspect of the present invention provides an application of the adhesive prepared by the above-described preparation method in wood processing, wherein the application method includes the following steps:

[0020] Step S1: Spray water to moisten the surface of the wood board, and then spray γ-glycidyl etheroxypropyltrimethoxysilane (KH560) onto the surface of the wood board;

[0021] Step S2: Apply the starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion to the wood surface;

[0022] Step S3: Press the wooden boards together and heat them to cure, and you will get multi-layer plywood.

[0023] Further, in step S1, the spraying amount of the γ-glycidyl etheroxypropyltrimethoxysilane is ≥80 mL / m. 2 .

[0024] Further, in step S2, the coating amount of the adhesive is ≥200g / m². 2 .

[0025] Furthermore, in step S3, the pressing pressure is 0.6 to 1.2 MPa, the heating and curing temperature is ≥100℃, and the time is ≥30 min.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] This invention provides a method for preparing a strong, hot water-resistant, starch-based, all-biomass green adhesive and its application in wood processing. The invention first prepares a starch-based adhesive using high-amylose starch and tannic acid as raw materials. Then, the wood surface is treated with KH560. Next, the starch-based adhesive is applied to the wood board, pressed, and dried to obtain plywood. This plywood will not delaminate even after being soaked in 30°C or 60°C hot water for 3 hours, meeting the requirements for Class II plywood in the national standard.

[0028] Specifically, the present invention has the following advantages:

[0029] (1) The starch-based adhesive prepared by this invention uses biomass raw materials, and the process is simple, with no waste generated. The production process is green and environmentally friendly, completely eliminating formaldehyde adhesives, and is safe and non-toxic when used.

[0030] (2) The starch-based adhesive prepared by the present invention has excellent performance. Plywood produced with it will not delaminate after being soaked in room temperature water and 60°C hot water for 3 hours, which meets the requirements of the national standard GB / T 17657-2022.

[0031] (3) The starch-based adhesive prepared by the present invention is suitable for the processing of all wood products, and can meet the application requirements of wood bonding and wood product processing, with a wide range of applications. Attached Figure Description

[0032] Figure 1 The graph shows a comparison of the shear strength of the plywood in Examples 1-4 and Comparative Examples 1-3 after being immersed in water at 30°C and 60°C for 3 hours. Detailed Implementation

[0033] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0035] Example 1: A method for preparing a starch-based adhesive and its application in wood processing.

[0036] (1) Weigh 0.4g of sodium hydroxide and add it to 25mL of water. Stir well to obtain NaOH solution. Then weigh 12.5g of high amylose (amylose content is 55%) and add it to NaOH solution. Stir well to obtain starch emulsion.

[0037] (2) Weigh 0.65g of calcium chloride and add it to 12.5mL of water. Stir well to obtain CaCl2 solution. Then add the obtained CaCl2 solution to the starch emulsion in step (1) and stir well to obtain starch solution.

[0038] (3) Weigh 2.5g of tannic acid powder and add it to 5mL of water. Stir well and then add the resulting solution to the starch solution in step (2). Stir well to obtain a mixed system.

[0039] (4) Add 1 mol / L hydrochloric acid to the mixture in step (3) to adjust the pH of the system to 6.5, then stir at 120 rpm, heat to 98°C, and keep warm at this temperature for 30 min to obtain starch / tannic acid paste.

[0040] (5) Add 3 mol / L NaOH to the starch / tannic acid paste from step (4), adjust the pH of the system to 9, then stir at 120 rpm and keep warm at 75°C for 30 min to obtain starch-based adhesive.

[0041] (6) Apply 250mm to the surface of the wooden board. 2 Spray a small amount of water to moisten, then spray 20μL of KH560, and then apply 0.05g of the starch-based adhesive from step (4).

[0042] (7) Press the multiple wooden boards obtained in step (6) together and cure them at 100°C for 30 minutes to obtain multi-layer plywood.

[0043] Example 2: A method for preparing a starch-based adhesive and its application in wood processing.

[0044] (1) Weigh 0.2g of sodium hydroxide and add it to 12.5mL of water. Stir well to obtain NaOH solution. Then weigh 6.25g of high amylose (amylose content is 55%) and add it to NaOH solution. Stir well to obtain starch emulsion.

[0045] (2) Weigh 0.4g of calcium chloride and add it to 8mL of water. Stir well to obtain CaCl2 solution. Then add the obtained CaCl2 solution to the starch emulsion in step (1) and stir well to obtain starch solution.

[0046] (3) Weigh 5g of tannic acid powder and add it to 10mL of water. Stir well and then add the resulting solution to the starch solution in step (2). Stir well to obtain a mixed system.

[0047] (4) Add 1 mol / L hydrochloric acid to the mixture in step (3) to adjust the pH of the system to 6.5, then stir at 120 rpm, heat to 98°C, and keep warm at this temperature for 30 min to obtain starch / tannic acid paste.

[0048] (5) Add 3 mol / L NaOH to the starch / tannic acid paste from step (4), adjust the pH of the system to 9, then stir at 120 rpm and keep warm at 75°C for 30 min to obtain starch-based adhesive.

[0049] (6) Apply 250mm to the surface of the wooden board. 2 Spray a small amount of water to moisten, then spray 20μL of KH560, and then apply 0.05g of the starch-based adhesive from step (4).

[0050] (7) Press the multiple wooden boards obtained in step (6) together and cure them at 100°C for 30 minutes to obtain multi-layer plywood.

[0051] Example 3: A method for preparing a starch-based adhesive and its application in wood processing.

[0052] (1) Weigh 0.4g of sodium hydroxide and add it to 25mL of water. Stir well to obtain NaOH solution. Then weigh 15g of high amylose (amylose content is 55%) and add it to NaOH solution. Stir well to obtain starch emulsion.

[0053] (2) Weigh 0.9g of calcium chloride and add it to 15mL of water. Stir well to obtain CaCl2 solution. Then add the obtained CaCl2 solution to the starch emulsion in step (1) and stir well to obtain starch solution.

[0054] (3) Weigh 6.25g of tannic acid powder and add it to 12.5mL of water. Stir well and then add the resulting solution to the starch solution in step (2). Stir well to obtain a mixed system.

[0055] (4) Add 1 mol / L hydrochloric acid to the mixture in step (3) to adjust the pH of the system to 6.5, then stir at 120 rpm, heat to 98°C, and keep warm at this temperature for 30 min to obtain starch / tannic acid paste.

[0056] (5) Add 3 mol / L NaOH to the starch / tannic acid paste from step (4), adjust the pH of the system to 9, then stir at 120 rpm and keep warm at 75°C for 30 min to obtain starch-based adhesive.

[0057] (6) Apply 250mm to the surface of the wooden board. 2 Spray a small amount of water to moisten, then spray 20μL of KH560, and then apply 0.05g of the starch-based adhesive from step (4).

[0058] (7) Press the multiple wooden boards obtained in step (6) together and cure them at 100°C for 30 minutes to obtain multi-layer plywood.

[0059] Example 4: A method for preparing a starch-based adhesive and its application in wood processing.

[0060] (1) Weigh 0.4g of sodium hydroxide and add it to 25mL of water. Stir well to obtain NaOH solution. Then weigh 12.5g of high amylose (amylose content is 68%) and add it to NaOH solution. Stir well to obtain starch emulsion.

[0061] (2) Weigh 0.9g of calcium chloride and add it to 15mL of water. Stir well to obtain CaCl2 solution. Then add the obtained CaCl2 solution to the starch emulsion in step (1) and stir well to obtain starch solution.

[0062] (3) Weigh 2.5g of tannic acid powder and add it to 5mL of water. Stir well and then add the resulting solution to the starch solution in step (2). Stir well to obtain a mixed system.

[0063] (4) Add 1 mol / L hydrochloric acid to the mixture in step (3) to adjust the pH of the system to 6.5, then stir at 120 rpm, heat to 98°C, and keep warm at this temperature for 30 min to obtain starch / tannic acid paste.

[0064] (5) Add 3 mol / L NaOH to the starch / tannic acid paste from step (4), adjust the pH of the system to 9, then stir at 120 rpm and keep warm at 75°C for 30 min to obtain starch-based adhesive.

[0065] (6) Apply 250mm to the surface of the wooden board. 2 Spray a small amount of water to moisten, then spray 20μL of KH560, and then apply 0.05g of the starch-based adhesive from step (4).

[0066] (7) Press the multiple wooden boards obtained in step (6) together and cure them at 100°C for 30 minutes to obtain multi-layer plywood.

[0067] Comparative Example 1: A method for preparing a starch-based adhesive and its application in wood processing.

[0068] Steps (1)-(2) and (4)-(7) are the same as the corresponding steps in Example 1, except for step (3). In step (3) of this comparative example, the mass ratio of tannic acid to high amylose is only 10% (less than 20%), and the other parameters are the same.

[0069] The shear strength of the bonded wood board after immersing in water at 30℃ for 3 hours was 0.71±0.18MPa, and the shear strength after immersing in hot water at 60℃ was 0.51±0.11MPa. This indicates that the bonded wood board in this comparative example has poor hot water resistance and does not meet the requirements of the national standard (GB / T9846-2015).

[0070] Comparative Example 2: A method for preparing a starch-based adhesive and its application in wood processing.

[0071] Steps (1)-(5) and (7) are the same as the corresponding steps in Example 2, except for step (6). In step (6) of this comparative example, the wood board surface was not treated with KH560, and the other parameters were the same.

[0072] The shear strength of the bonded wood board after immersing in water at 30℃ for 3 hours was 0.52±0.07MPa, and the shear strength after immersing in hot water at 60℃ was 0.17±0.15MPa. This indicates that the bonded wood board in this comparative example has poor hot water resistance and does not meet the requirements of the national standard (GB / T9846-2015).

[0073] Comparative Example 3: A method for preparing a starch-based adhesive and its application in wood processing.

[0074] Steps (2)-(7) are the same as the corresponding steps in Example 2, except for step (1). The high amylose used in step (1) of this comparative example is ordinary starch (amylose content is 27%), and the other parameters are the same.

[0075] The shear strength of the bonded wood board after immersing in water at 30℃ for 3 hours was 0.57±0.06MPa, and the shear strength after immersing in hot water at 60℃ was 0.45±0.05MPa. This indicates that the bonded wood board in this comparative example has poor hot water resistance and does not meet the requirements of the national standard (GB / T9846-2015).

[0076] After immersing the plywood from Examples 1-4 and Comparative Examples 1-3 in water at 30°C and 60°C for 3 hours, respectively, the corresponding shear strength was tested, and the comparison graphs are shown below. Figure 1 As shown, the plywood prepared according to Examples 1, 2, 3, and 4 exhibits significantly higher tear shear strength than the national standard of 0.7 MPa, regardless of whether it is soaked in water at 30°C for 3 hours or at 60°C for 3 hours. In contrast, the plywood prepared according to Comparative Examples 1, 2, and 3 shows tear shear strength less than 0.7 MPa after soaking in water (especially at 60°C).

[0077] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A method for preparing a starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion, characterized in that, The preparation method includes the following steps: (1) Add high amylose to NaOH solution to obtain starch emulsion; (2) Add CaCl2 solution to starch emulsion; (3) Add tannic acid solution to starch emulsion in step (2), adjust pH value, heat and keep warm to make hot starch paste; (4) Add NaOH solution to hot starch paste, adjust pH to 9-10, keep warm and stir to obtain starch-based whole biomass green adhesive with strong adhesion and resistance to hot water soaking.

2. The method for preparing a starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion according to claim 1, characterized in that, In step (1), the high amylose refers to natural starch with an amylose content of more than 50% in starch granules.

3. The method for preparing a starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion according to claim 1, characterized in that, In step (1), the mass concentration of the NaOH solution is ≥1%, and the mass ratio of the high amylose to the NaOH solution is ≤3:

5.

4. The method for preparing a starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion according to claim 1, characterized in that, In step (2), the mass concentration of the CaCl2 solution is ≥5%, and the mass ratio of CaCl2 to high amylose is ≥5%.

5. The method for preparing a starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion according to claim 1, characterized in that, In step (3), the mass ratio of tannic acid to high amylose is ≥1:5, and the pH value is 6.5-7.

6. The method for preparing a starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion according to claim 1, characterized in that, In step (4), the temperature of the heat preservation is ≥75℃ and the heat preservation time is ≥30min.

7. The application of an adhesive prepared by the preparation method according to any one of claims 1-6 in wood processing, characterized in that, The method of application includes the following steps: Step S1: Spray water to moisten the surface of the wood board, and then spray γ-glycidoxypropyltrimethoxysilane onto the surface of the wood board; Step S2: Apply the starch-based all-biomass green adhesive with strong adhesion and resistance to hot water immersion to the wood surface; Step S3: Press the wooden boards together and heat them to cure, and you will get multi-layer plywood.

8. The application of the adhesive according to claim 7 in wood processing, characterized in that, In step S1, the spraying amount of the γ-glycidyl etheroxypropyltrimethoxysilane is ≥80 mL / m. 2 .

9. The application of the adhesive according to claim 7 in wood processing, characterized in that, In step S2, the coating amount of the adhesive is ≥200g / m². 2 .

10. The application of the adhesive according to claim 7 in wood processing, characterized in that, In step S3, the pressing pressure is 0.6 to 1.2 MPa, the heating and curing temperature is ≥100℃, and the time is ≥30 min.

Citation Information

Patent Citations

  • Preparation method and application of starch-based waterproof flame-retardant adhesive

    CN115340832A

Cited By

  • A starch-based non-isocyanate polyurethane wood adhesive and a preparation method thereof

    CN122587645A